Ngapartji Ngapartji In turn, in turn: Ego-histoire, Europe and Indigenous Australia - Castejon, Vanessa; Cole, Anne; Haag, Oliver; Hughes, Karen (ANU Press, 2014)
In this innovative collection, Indigenous and non-Indigenous scholars from Australia and Europe reflect on how their life histories have impacted on their research in Indigenous Australian Studies.